Using jigsaw strategy in teaching chemistry on developing critical thinking and motivation - Shehada, Fawaz Hassan; Aya Al- Hihi, Ahmad Ali Alsyouf (Opción, 2020)
This research aimed to identify the effect of using Jigsaw strategy in teaching chemistry on developing critical thinking and motivation for 10th grade female students in Al-Zarqa’a Governorate. The study applied two tools, critical thinking test and motivation scale. The results showed that there were statistically significant differences between the mean performance of the two groups on the critical thinking test and the motivation scale, in favor of the experimental study group, which was studied the chemistry course by using the Jigsaw strategy. In conclusion, the Jigsaw strategy had a positive role in developing the corporation and love.